2009
DOI: 10.1088/0004-637x/701/1/306
|View full text |Cite
|
Sign up to set email alerts
|

Clumpy Galaxies in Goods and Gems: Massive Analogs of Local Dwarf Irregulars

Abstract: Clumpy galaxies in the Galaxy Evolution from Morphology and SEDs and Great Observatories Origins Deep Survey fields are examined for clues to their evolution into modern spirals. The magnitudes of the clumps and the surface brightnesses of the interclump regions are measured and fitted to models of stellar age and mass. There is an evolutionary trend from clump clusters with no evident interclump emission to clump clusters with faint red disks, to spiral galaxies of the flocculent or grand design types. Along … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
219
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(241 citation statements)
references
References 107 publications
(146 reference statements)
15
219
1
Order By: Relevance
“…Cresci et al 2009;Epinat et al 2009;Law et al 2009). Because the Jeans length L J in a gas rich system is proportional to (σ/V) 2 (Genzel et al 2008), this supports the idea that the clumpy morphology of both high redshift disks and blue dwarf galaxies comes from gravitational instabilities in gas with high turbulent speed compared to the rotation speed, and a high mass fraction compared to the stars (see Elmegreen et al 2009). …”
Section: Gas Kinematicssupporting
confidence: 52%
See 1 more Smart Citation
“…Cresci et al 2009;Epinat et al 2009;Law et al 2009). Because the Jeans length L J in a gas rich system is proportional to (σ/V) 2 (Genzel et al 2008), this supports the idea that the clumpy morphology of both high redshift disks and blue dwarf galaxies comes from gravitational instabilities in gas with high turbulent speed compared to the rotation speed, and a high mass fraction compared to the stars (see Elmegreen et al 2009). …”
Section: Gas Kinematicssupporting
confidence: 52%
“…These clusters could be the progenitors of the old globular clusters observed in most galaxies today (de Grijs & Parmentier 2007), thus providing further evidence for the link between the starburst phenomenon and the formation of galaxies. Moreover, star-forming regions with properties consistent with the more massive HII regions detected locally are observed up to z ∼ 5 (Swinbank et al 2009), and local dwarf galaxies have been identified as scaled down analogs of clumpy starforming galaxies at high redshift (Elmegreen et al 2009). Dwarf for He 2-10, the clusters (L1-6) from Cabanac et al (2005) and the radio knots (knot 1-5) from Kobulnicky & Johnson (1999) are marked, while for NGC 5253 the clusters from Calzetti et al (1997) and Vanzi & Sauvage (2004).…”
Section: Introductionmentioning
confidence: 93%
“…With the higher dispersions necessary to keep the disk near the line of stability suggests that the disks are generally thicker than disks in the local universe as perhaps observed (e.g. Elmegreen et al 2009;Epinat et al 2012). …”
Section: Scenario Within the Context Of Distant Galaxiesmentioning
confidence: 92%
“…Glazebrook et al 1995;Abraham et al 1996a,b;van den Bergh et al 1996;Cowie et al 1995;Im et al 1999;Elmegreen et al 2004Elmegreen et al , 2005Elmegreen et al , 2007bElmegreen et al , 2009Förster Schreiber et al 2009 with large SFR in excess of 100 M year −1 (e.g. Bauer et al 2011).…”
Section: The Role Of Mergersmentioning
confidence: 99%